Physical activity combined with sedentary behaviour in the risk of mortality in older adults - Galvão, Lucas Lima; Silva, Rizia Rocha; Tribess, Sheilla; Santos, Douglas Assis Teles; Junior, Jair Sindra Virtuoso (Revista de Saúde Pública, 2021)
OBJECTIVE To examine the effects of physical activity (PA) and sedentary behaviour (SB), in isolation and combination, on all-cause mortality in older adults. METHODS Prospective, population-based cohort study. The data were collected from first wave in 2015 and the follow-up continued until 2020. The sample consisted of 332 older adult people aged ≥ 60 years-old, out of which 59 died. The level of PA and SB was assessed by the International Physical Activity Questionnaire (IPAQ). The older adults were divided into PA categorized as sufficiently active and insufficiently active and into high and low SB. We built four combinations of PA and SB. Also, we used the Cox proportional hazards regression with a 95% confidence interval with hazard ratio estimate so as to verify the mortality risks between PA, SB, and the combinations of PA and SB. RESULTS Insufficiently active individuals had higher risks of mortality compared to sufficiently active people. We observed no associations between SB and mortality separately; however, when evaluated in a combined way, insufficiently active individuals and with a high SB time had a higher chance of mortality compared to active individuals with a low SB time. CONCLUSION Our isolated analyses demonstrate that complying with PA recommendations reduces the risk of mortality; however, no association was found between the time of PA exposure with the time of SB. When analysing the combination, being physically inactive and with a long time of SB showed higher mortality rates, with SB being an enhancer of this risk. The results of this study show the interdependence of SB for PA performed at moderate to vigorous intensity. The understanding of this interrelation must be considered in the formulation of public health guidelines.